Enhancing Royal grape quality through a three-year investigation of soil management practices and organic amendments on berry biochemistry - Ozkan Kaya; Sinem Karakus; Fadime Ates; Selda Daler; Harlene Hatterman-Valenti (Chemical and Biological Technologies in Agriculture)
Abstract Background Grape composition, characterized by mineral content, hormone levels, and antioxidant enzyme activities, fundamentally influences berry quality, nutritional value, and vine health. Various viticultural practices, particularly tillage methods and organic fertilization techniques, significantly impact these compositional parameters. This study investigates the effects of these agricultural practices on grape composition to establish optimal protocols for enhanced berry production and quality. Methods A three year study (2020–2022) evaluated the effects of soil management on grape quality in ‘Royal’ grapes (VIVC: 349). Using a Randomized Complete Block Design with four replicates of 12 vines, the study tested three tillage methods (chisel, disc harrow, and no-tillage) and four organic fertilizers (Antep radish, broccoli, olive blackwater, and a control). Treatments were analyzed for berry mineral content (macro and micronutrients), hormone levels (auxin, ABA, zeatin, SA, JA, cytokinin and GA), and antioxidant enzyme activities (SOD, POD, CAT, APX, GR, GST, G6PD and 6PGD). Results Based on our results, the disc harrow tillage method in conjunction with olive blackwater fertilizer demonstrated superior mineral accumulation, yielding peak concentrations of nitrogen (3.72%), phosphorus (0.40%), and magnesium (0.41 mg/kg) during the 2021 growing season. Endogenous hormone levels exhibited treatment-specific responses, with maximum indole-3-acetic acid (17.33 ng/g) accumulation observed under no tillage control conditions in 2022, while abscisic acid concentrations peaked (49,172.53 ng/g) under no tillage with broccoli fertilization. Antioxidant enzyme activities were significantly enhanced under chisel tillage combined with broccoli fertilizer treatment, leading to optimal superoxide dismutase (1426.54 EU) and peroxidase (14,936.81 EU) activities. Principal component analysis revealed that the first two components explained 51.35% of total variance, with distinct temporal clustering of treatment effects. Conclusion The optimal cultivation practice for ‘Royal’ grape variety was determined to be chisel tillage method combined with broccoli fertilization, which maximized both mineral nutrient content and hormone levels. These findings provide practical insights for viticulturists to optimize cultivation techniques for improved grape quality and nutritional value. Graphical Abstract